Natural-scientific Prose in Croatian [Childrenʼs] Literature - Batinić , Ana (Poznańskie Studia Slawistyczne, 2021)
Natural-scientific prose is characterized by a specific description of the natural world in which scientific information is fitted in the experience of nature and animal characters only partially or minimally anthropomorphized. The goal of this research is firstly to explore the presence and influence of foreign literary authors in the history of Croatian (childrenʼs) literature, who dedicated their literary work to this unique literary subgenre, such as a Danish journalist and writer Carl Ewald and an American-Canadian zoologist and literary author Ernest Thompson Seton. Furthermore, the aim of the paper was also to study the contribution of Croatian authors – Miroslav Hirtz, Zlatko Špoljar, Antica Juras-Ljubić and Vlatko Šarić – in this narrative form by methodologically relying on the insights of literary science and animal studies.